Pancasila Sebagai Dasar Sistem Kesejahteraan Masyarakat Indonesia - Lukas Pattipeilohy; Yakobus Adi Saingo (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The aim of this research is to discuss Pancasila as the basis of the welfare sistem of Indonesian society. The method used in this research is in the form of a literature study which obtains supporting information from various scientific references from journals, proceedings, scientific articles, academic books related to the theme of discussion. Data were analyzed using a descriptive approach to provide an overview of Pancasila as a welfare sistem which is the basis for the activities of all Indonesian society. The results of this research are that Pancasila as a welfare sistem reflects the philosophical principles and basic values that underlie Indonesia's social, political and economic order. Pancasila as a welfare sistem can be viewed as: Pancasila as a Philosophical Foundation, Social Justice, Social Welfare, Political and Economic Democracy, Social Protection. Indonesian people must understand that Pancasila is not only a guide for the government, but also a shared responsibility of all Indonesian people in creating a just and prosperous society. This includes efforts to provide basic needs services, maintain economic justice, ensure inclusive democracy, and protect human rights. Thus, Pancasila plays an important role in efforts to achieve prosperity and justice for all Indonesian people.